A DISCOURSE ANALYSIS OF SONG ENTITLED "GHOST" BY JUSTIN BIEBER - Caroline Devi Mareta; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to analyze the form of discourse analysis of songs entitled “Ghost” by Justin Bieber. The researcher used a qualitative descriptive method. The data collection in the research was listening, watching, reading and taking notes all data from the song. The researcher used the validity triangulation data and triangulation theory to check validation. The result of the research showed that in song entitled “Ghost” by Justin Bieber was divided into three aspects, they were socio cultural aspect, grammatical aspect (reference and conjunction) and lexical aspect (repetition and collocation). All aspects were important in understanding the context of the song. Key words: Discourse Analysis, Song, Justin Bieber.